1998
DOI: 10.1002/(sici)1521-1878(199806)20:6<453::aid-bies3>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of life cycles with haploid and diploid phases

Abstract: Sexual eukaryotic organisms are characterized by an alternation between haploid and diploid phases. In vascular plants and animals, somatic growth and development occur primarily in the diploid phase, with the haploid phase reduced to the gametic cells. In many other eukaryotes, however, growth and development occur in both phases, with substantial variability among organisms in the length of each phase of the life cycle. A number of theoretical models and experimental studies have shed light on factors that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
177
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(178 citation statements)
references
References 63 publications
0
177
0
1
Order By: Relevance
“…Thus in scolytids it is now possible to compare diplodiploid and haplodiploid sister groups that can both be unambiguously inferred to occupy the same ancestral environment and to have (apart from dispersal and breeding biology) largely the same ancestral habits. In no other case is this now possible (Beutel & Haas 1996;Blaxter et al 1998;Crespi et al 1996;Garey et al 1996;Hoernschemeyer 1998;Mable & Otto 1998;Von Dohlen & Moran 1995;White 1973;Whiting et al 1997), though future phylogenetic analyses may ultimately make it possible in other cases, especially in scale insects and mites (Norton et al 1993;Nur 1980).…”
Section: Discussion (A) Ecology and Diversi¢cation Of Haplodiploid Scmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus in scolytids it is now possible to compare diplodiploid and haplodiploid sister groups that can both be unambiguously inferred to occupy the same ancestral environment and to have (apart from dispersal and breeding biology) largely the same ancestral habits. In no other case is this now possible (Beutel & Haas 1996;Blaxter et al 1998;Crespi et al 1996;Garey et al 1996;Hoernschemeyer 1998;Mable & Otto 1998;Von Dohlen & Moran 1995;White 1973;Whiting et al 1997), though future phylogenetic analyses may ultimately make it possible in other cases, especially in scale insects and mites (Norton et al 1993;Nur 1980).…”
Section: Discussion (A) Ecology and Diversi¢cation Of Haplodiploid Scmentioning
confidence: 99%
“…A much closer relationship between Xyleborini and inbreeding Dryocoetini, implying a single origin of haplodiploidy, was suggested by Browne (1959), on the basis of adult morphology, by Lekander (1968), on the basis of larval characters, and by Nobuchi (1969), on the basis of characters of the proventriculus, but none of these authors presented a formal analysis supporting these suggestions or a formal classi¢-cation re£ecting them. A recent review of haplodiploidy draws attention to this lack of agreement regarding the number of origins in Scolytidae (Mable & Otto 1998). To help resolve this question, we have studied the phylogenetic relationships of inbreeding haplodiploid scolytids using nuclear (elongation factor 1-a (ef-1a)) and mitochondrial (cytochrome oxidase 1 (co1)) DNA sequences.…”
Section: Introductionmentioning
confidence: 99%
“…They are found in Rotifera, Nematoda, Arachnida and a significant fraction of the Insecta (Mable and Otto, 1998). Koevoets and Beukeboom (2009) found some support for the haploid males being more strongly negatively affected by hybridization than hybrid diploid females (although the number of studies was very limited) and suggested to rephrase HR to apply to 'the heterogametic or hemizygous sex'.…”
Section: Haplodiploidsmentioning
confidence: 99%
“…Consequently, the evolutionary and ecological aspects of this variation have been given considerable attention (Valero et al 1992, Richerd et al 1993, Mable and Otto 1998, Hughes and Otto 1999, Thornber 2006. Algal life cycles differ in the relative timing of syngamy and meiosis, and the degree of mitotic activity in the haploid and diploid phases (Coelho et al 2007, Figure 1).…”
Section: Introductionmentioning
confidence: 99%